Navigating the landscape of PD-1/PD-L1 imaging tracers: from challenges to opportunities - Badenhorst, Melinda; Windhorst, Albert D.; Beaino, Wissam (Frontiers in Medicine, 2024)
Immunotherapy targeted to immune checkpoint inhibitors, such as the program cell death receptor (PD-1) and its ligand (PD-L1), has revolutionized cancer treatment. However, it is now well-known that PD-1/PD-L1 immunotherapy response is inconsistent among patients. The current challenge is to customize treatment regimens per patient, which could be possible if the PD-1/PD-L1 expression and dynamic landscape are known. With positron emission tomography (PET) imaging, it is possible to image these immune targets non-invasively and system-wide during therapy. A successful PET imaging tracer should meet specific criteria concerning target affinity, specificity, clearance rate and target-specific uptake, to name a few. The structural profile of such a tracer will define its properties and can be used to optimize tracers in development and design new ones. Currently, a range of PD-1/PD-L1-targeting PET tracers are available from different molecular categories that have shown impressive preclinical and clinical results, each with its own advantages and disadvantages. This review will provide an overview of current PET tracers targeting the PD-1/PD-L1 axis. Antibody, peptide and antibody fragment tracers will be discussed with respect to their molecular characteristics and binding properties and ways to optimize them.